2016
DOI: 10.1007/s00737-016-0657-x
|View full text |Cite
|
Sign up to set email alerts
|

Are participants in face-to-face and internet support groups the same? Comparison of demographics and depression levels among women bereaved by stillbirth

Abstract: Support groups can help individuals cope with difficult health situations but have been understudied for women with perinatal bereavement. An early study suggested those using internet support groups had high rates of positive depression screens, raising the question whether these users were more symptomatic than those in similar face-to-face support groups. We therefore conducted two convenience sample surveys of women bereaved by perinatal loss, one looking at use of online support groups and the other in-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Additionally, RRESDO may be more acceptable than RRSO for combined surgery given the potential for menopausal symptoms while recovering from effects of mastectomy. Benefits of OSGs [42][43][44] include fluid informational exchange, continuous availability, greater access/anonymity and were also reported by our cohort. Our cohort reported increasing anxiety with OSGs and a preference for educational support groups (ESGs).…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, RRESDO may be more acceptable than RRSO for combined surgery given the potential for menopausal symptoms while recovering from effects of mastectomy. Benefits of OSGs [42][43][44] include fluid informational exchange, continuous availability, greater access/anonymity and were also reported by our cohort. Our cohort reported increasing anxiety with OSGs and a preference for educational support groups (ESGs).…”
Section: Discussionsupporting
confidence: 68%
“…In a similar study, Gold et al (2016) found no differences in depression levels for bereaved mothers who received peer support via the Internet versus a faceto-face mode. A study on suicide survivors in the Netherlands reported decreases in depression and increased well-being over a 12-month period for participants in an Internet only support group (Kramer et al, 2015).…”
Section: Internet-based Peer Supportmentioning
confidence: 85%
“…Of high quality studies that assessed peer support effectiveness, six of the seven found significant benefits for bereaved persons who received peer support, either in terms of reduced grief symptoms or increased personal growth. One study (Gold, Normandin, & Boggs, 2016) found no difference in depression symptoms between bereaved mothers who received peer support via the Internet versus face-to-face peer support. In this case, however, both groups reported that peer support was helpful in reducing the sense of isolation.…”
Section: Benefits Of Peer Support For Bereaved Survivorsmentioning
confidence: 99%
“…This was accomplished through Cognitive Behavioural Therapy using computers [ 46 ], and web-based decision aid for understanding fetal anomalies [ 47 ]. Educational text messages were sent to encourage breastfeeding [ 79 ], and general health promotion interventions were delivered as well [ 43 , 44 , 56 , 65 , 73 , 75 , 80 ].…”
Section: Resultsmentioning
confidence: 99%